Asymmetric mandible identification using Cone Beam Computed Tomography (CBCT) - Barunawaty Yunus; Zulfikar R. Mailili; Dwi P. Wulansari (DiscoverSys Inc., 2019)
Objective: To determine the prevalence of patients with asymmetric mandible based on age, gender, and severity that examined using CBCT section of the Dental and Oral Hospital of Hasanuddin University.Material and Methods: Secondary data from dental records (CBCT data) of patients at Dental and Maxillofacial Department in Dental and Oral Hospital of Hasanuddin University from January 2014 - March 2016 were examined. The data collected to calculate the prevalence of asymmetric mandible from CBCT image and then presented in tabular form.Results: From this research it is found that the age group 36-50 years was the top ranked in prevalence of asymmetric mandible, and there is no significant difference between the number of male and female patients.Conclusion: Asymmetric mandible caused by pathological factors have the highest incident